Sebuah PELATIHAN PEMBUATAN KARYA MOZAIK BERTEMA CERITA RAKYAT BERBAHAN LIMBAH KACA - Novia Nur Kartikasari; Nooryan Bahari; Joko Lulut Amboro; Novita Wahyuningsih (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
The service focuses on training on processing glass waste as the main ingredient in making mosaic works, themed on folklore. Aims to provide knowledge about the potential of glass waste, and the technical practice of processing it to become a mosaic work. The training participants were a group of young people from Noloro, located in Sawit, Panggungharjo, Bantul DIY. The method used in the implementation is ADDIE, which stands for the stages of the process itself, namely Analysis, Design, Develop, Implement, and Evaluate. The result of the training is a mosaic work from glass waste, taking the theme of one of the folk tales from Bantul Regency, namely about the Krapyak Stage as well because it is a very iconic building.